Factors Affecting Grade 12 Learners Performances: Analysis using Propensity Score Methods - Sibanda, Emmanuel; Mathye, Peter; Masebe, Tshidiso Punch; Rankhumise, Mmushetji Petrus (Department of Mathematics Education University of Muhammadiyah Malang, 2025)
This research examines the impact of pre-existing disparities on Grade 12 examination performance in Gauteng and the Western Cape Provinces of South Africa, utilising propensity score matching to balance influencing factors. The analysis focuses on learners from both provinces who participated in Grade 12 examinations from 2017 to 2019. Based on the 2017 datasets, it was found that learners in the Western Cape had significantly lower odds of passing compared to those in Gauteng when using unmatched datasets. However, after matching, the likelihood of passing for Western Cape learners improved to 69%, though they remained less likely to pass than their Gauteng counterparts. This trend was observed for the years 2018 and 2019. These findings emphasise the importance of using matched data to avoid misleading conclusions in comparative assessments of educational performance.